Characterization of Ciprofloxacin Resistance Levels: Implications for Ototopical Therapy. Issue 7 (August 2021) - Trinh, Katherine V.; Ruoff, Kathryn L.; Rees, Christiaan A.; Ponukumati, Aravind S.; Martin, Isabella W.; O'Toole, George A.; Saunders, James E.
Abstract : Hypothesis: Ciprofloxacin-resistant pathogens are inhibited by high concentrations of ciprofloxacin found in commercially-available ototopical solutions. Background: Ciprofloxacin-resistant pathogens in otitis media are currently treated with ototopical ciprofloxacin suspensions. This is done irrespective of laboratory-reported ciprofloxacin susceptibility, under the assumption that the high concentration of ciprofloxacin applied topically is sufficient to overcome antimicrobial resistance. Methods: We evaluated 34 ciprofloxacin-resistant isolates consisting of Staphylococcus aureus, Pseudomonas aeruginosa, Corynebacterium spp., and Turicella otitidis . Ciprofloxacin minimum inhibitory concentration (MIC) assays and clinical ototopical solution minimum bactericidal concentration (CMBC) assays were performed. Results: Amongst the ciprofloxacin-resistant isolates, ciprofloxacin MICs ranged from 8 to 256 mcg/ml (mean: 87.1 mcg/ml) and CMBCs ranged from 23.4 to 1500 mcg/ml (mean: 237.0 mcg/ml). There were no significant differences with respect to MIC in comparing P. aeruginosa versus Corynebacterium spp. (mean: 53.3 versus 55.2, p  = 0.86), S. aureus versus P. aeruginosa (mean: 128.0 versus 53.3, p  = 0.34), and S. aureus versus Corynebacterium spp. (mean: 128.0 versus 55.2, p  = 0.09). The correlation between ciprofloxacin MIC and CMBC was poor (Pearson's r  = –0.08, p  = 0.75). Conclusions: Ciprofloxacin-resistant pathogens commonly recovered from otitis media exhibit highly variable ciprofloxacin MIC and CMBC levels. Ciprofloxacin was able to inhibit growth in all isolates tested at MIC levels less than or equal to 256 mcg/ml; however, CMBC's up to 1500 mcg/ml were observed within that same group. The clinical relevance of these in vitro MICs is unclear due in part to higher bactericidal concentrations (CMBC) in several strains. Our results suggest that treatment failures may be due to a combination of factors rather than high-level resistance alone.